Preparation Of Physical Exercises And Techniques Of Futsal Game For Teachers, Trainers And Coaches Of Futsal In Sijunjung District - Roma Irawan; Vega Soniawan; Heru Syarli Lesmana (Jurnal Berkarya Pengabdian Masyarakat, 2019)
Still many coaches are not yet understood to compose the form of practice ranging from physical exercises, techniques. Physical exercises range from mild to heavy and fun exercise forms. As for the training techniques, many trainers are less familiar starting from the term Practice Series (basic/Basic,) until the situation play for some techniques in futsal sports. This activity was conducted by coordinating through partners on 03 October 2019 at the Office of the Education and Culture department Sijunjung district. Agreed on activities held on 18 until 20 October 2019. The activity lasts 3 days (starting on the first day of 14.00 S/d 18.00 WIB and resumed on the next 2 days starting at 08.00 S/d 18.00 WIB) on the Gor Sibinuang and Futsal field analyst. Activities are done by lecture, discussion and practice in the field. The result of this training process is; 1) All participants understand the forms of exercise of physical condition and the forms of technical exercises in Futsal sport demonstrated by some speakers, 2) the response and encouragement from local government is enough to be able to hold Futsal sports training activities by giving the local government permission, as well as the commitment of the local government to send some eligible participants to participate in the official training of the Associso futsal and will hold several matches to see the results of the activities undertaken. 3) Cooperation between TlM LP2M with FIK UNP and related elements running smoothly, 4) The participants ' enthusiasm is high enough to follow this activity, because this Futsal sport is a popular sport and favorite community